STRATEGI GURU DALAM PENGELOLAAN KELAS PADA PEMBELAJARAN DI SD INPRES 2 TOLAI - Yanti, Ni Ketut Januari; Narayanti, Putu Satya; Anta, I Made Nuhari (JATMIKA : Journal Education and Learning of Elementary School, 2024)
This study aims to determine the teacher's strategy in classroom management. the method used in this research is descriptive qualitative method. The research results obtained show that the teacher's strategies in classroom management in learning such as: conventional formation, chevron formation, group formation, U-shape formation, conference formation, auditorium formation, circle formation. the differences in teacher strategies in classroom management in the 2013 curriculum and the independent curriculum, namely: the 2013 curriculum uses conventional seating positions, chevron formations, group formations, U-shape formations and conference formations, while the independent curriculum uses auditorium formations and circle formations. In the teacher's strategy in classroom management there are several obstacles and supports that are commonly felt by teachers such as where the lack of cohesiveness of students has limited learning resources and the physical condition of the class is not good, while for supporting classroom management namely good communication between teachers and students, the atmosphere of the room is neat and clean make students comfortable while carrying out learning, decorations and blackboards are well attached.